Phytochemical Composition of the Extracts from Iresine herbstii and its Therapeutic use via Antioxidant and Cytotoxic Potential by Multiple In Vitro Assays - Dipankar Chaudhuri,; Murugan Sevanan, (International Journal of Phytomedicine, 2012)
Many plants have been known to synthesize active secondary metabolites to protect themselves which have potential therapeutic applications. Iresine herbstii leaf and stem powders were extracted using ethanol, acetone, dichloromethane and petroleum ether. Phytochemicals were investigated by Gas Chromatography-Mass Spectroscopy (GCMS) and the total phenolic content as well as their therapeutic potentials also investigated by multiple in vitro assays such as radical scavenging activity, Fe3+reducing power, total antioxidant capacity and cytotoxicity towards cancer cells. Ethanolic extract was subjected for spectroscopic phytochemical analysis and therapeutic uses of I. herbstii extracts were evaluated by different in vitro methods. The total phenolic content of the samples, analyzed using Folin–Ciocalteau reagent varied from 34.67±0.58 to 103.33±1.53 mg/g dry weight, expressed as gallic acid equivalents (GAE). The 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity of the extracts was increased in a dose dependent manner and found that acetone extract of stem exhibited highest activity when compared to standard ascorbic acid. Cytotoxic effect of ethanolic extract of leaf was examined in vitro in HeLa cervical cancer cell line by trypan blue assay and observed over 85% reduction in live cells. The results obtained in this study clearly indicate that I. herbstii has a significant potential to be used as a natural antioxidant and anticancer agent.